Handling Domestic Violence Perpetrator From Legal Perspective - Abidah Abdul Ghafar; Siti Nurleli Rusmiyati; Nurfadhilah Che Amani (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
In Malaysia, Domestic Violence Act 1984 is a piece of legislation that can provide civil protection in a domestic setting. When a case of abuse is committed by a perpetrator to one of the family members, this law may apply. This paper discusses the extent to which the Domestic Violence Act can provide protection to the victim as well as prevent the perpetrator from further harassing or abusing the victim. It also elaborates on the insight relating to the law on handling the perpetrator of domestic violence. It discusses the protection orders available for victims in order to safeguard themselves from further abuse and violence of the perpetrator. The recently developed Domestic Violence (Amendment) Act 2017 is referred for this purpose.